Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pelanggan Penyewa Lapangan Gedung Olahraga Angkasa Badminton Centre Pekanbaru - Dehotman, Khornelis (Sekolah Tinggi Ilmu Ekonomi Riau, 2023)
The research was carried out on tenant customers of the Angkasa Badminton center Pekanbaru sports building. In analyzing the data obtained from the research object using descriptive and quantitative methods, descriptive is comparing the actual reality with theories that have something to do with the problem in order to draw conclusions and tabulate it in tabular form and then analyze it according to the research objectives and quantitatively, namely by using statistical tools simple linear regression method to determine the relationship between the dependent variable (Y) with one independent variable (X). Judging from the calculation of the t-test, tcount (7.868) is greater than ttable (1.98969). So it can be concluded that H0 is rejected, meaning that there is a significant influence between service quality and customer satisfaction. Judging from the results of linear regression, that R2 is 43.3%, while 56.7% is influenced by other factors not examined in this study. This means that service quality has a moderate effect on customer satisfaction. In connection with the lack of maximum service quality, the leadership of the Angkasa Badminton Sports Hall must improve the quality of service to customers in order to increase customer satisfaction, so that customers feel satisfied with the service. It is better if a suggestion box is provided so that the management of Angkasa Badminton Sports Hall understands customer complaints